High-Level Language Production in Parkinson's Disease: A Review - Lori J. P. Altmann; Michelle S. Troche (Parkinson's Disease)
This paper discusses impairments of high-level, complex language production in Parkinson's disease (PD), defined as sentence and discourse production, and situates these impairments within the framework of current psycholinguistic theories of language production. The paper comprises three major sections, an overview of the effects of PD on the brain and cognition, a review of the literature on language production in PD, and a discussion of the stages of the language production process that are impaired in PD. Overall, the literature converges on a few common characteristics of language production in PD: reduced information content, impaired grammaticality, disrupted fluency, and reduced syntactic complexity. Many studies also document the strong impact of differences in cognitive ability on language production. Based on the data, PD affects all stages of language production including conceptualization and functional and positional processing. Furthermore, impairments at all stages appear to be exacerbated by impairments in cognitive abilities.